Sports Activities in Obese Teenagers Improve Social Inclusion and Health - Pietro Montesano; Filomena Mazzeo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Obesity is known to be a major risk of whole range of cardio vascular, metabolic and respiratory disorders. The etiology of obesity can be genetic, hormonal and determine the central obesity (or visceral or android). It is characterized by the deposit of fat especially abdominal and recognizable by a waist-hip ratio of more than 0.85 in women and 0.95 in 'man, and the peripheral (or subcutaneous or gynoid) that shows a ratio of less than 0.85 in women and 0.95 in men. The research was carried out in order to monitor and improve the correct use of the respiratory function of obese adolescents by developing a sports program aimed at reducing body weight and enhancing motor skills on 60 subjects (30 males and 30 females) aged between 14 and 16 years for a period of eight months. Results showed a reduction in body weight for almost all participants. For 26 subjects, the reduction was around 10%, while for others it was around 8%. Only 8 subjects did not significantly change their weight. The improvement of the motor program, on average, was about 9.5%. The phenomenon of obesity is often one of the factors of discomfort conditions in adolescence that slows down the process of social inclusion and highlights "paramorhism" that has negative effect on the respiratory function. Sport is one of the most important activities to combat the problem of weight gain because, through the rules of sports disciplines, it favors the acquisition of correct lifestyles.